Experimental Study of Hysteretic Steel Damper for Energy Dissipation Capacity - Daniel R. Teruna; Taksiah A. Majid; Bambang Budiono (Advances in Civil Engineering)
This study aims to evaluate energy absorption capacity of hysteretic steel damper for earthquake protection of structures. These types of steel dampers are fabricated from mild steel plate with different geometrical shapes on the side part, namely, straight, concave, and convex shapes. The performance of the proposed device was verified experimentally by a series of tests under increasing in-plane cyclic load. The overall test results indicated that the proposed steel dampers have similar hysteretic curves, but the specimen with convex-shaped side not only showed stable hysteretic behavior but also showed excellent energy dissipation capabilities and ductility factor. Furthermore, the load-deformation relation of these steel dampers can be decomposed into three parts, namely, skeleton curve, Bauschinger part, and elastic unloading part. The skeleton curve is commonly used to obtain the main parameters, which describe the behavior of steel damper, namely, yield strength, elastic stiffness, and postyield stiffness ratio. Moreover, the effective stiffness, effective damping ratio, cumulative plastic strain energy, and cumulative ductility factor were also derived from the results. Finally, an approximation trilinear hysteretic model was developed based on skeleton curve obtained from experimental results.